التكافؤ بين المتتاليات Mann Ishikawa, Noor, للتطبيقات ضعيفة التقليص - متيلج, عدنان (Latakia University Journal -Basic Sciences Series, 2018)
سنبرهن في هذه المقالة على التكافؤ بين تقارب المتتاليات ( Mann ، Ishikawa ، Noor ) من أجل صنف من التطبيقات ضعيفة التقليص contractive) (Weak والمعرفة على مجموعات جزئية و مغلقة و محدبة لفضاء كيفي. كما نبرهن أن التكافؤ يمدد إلى التطبيقات اللاتمددية المعممة ( (Generalized non expansive ضمن الشروط : على وسطاء التطبيق . أخيراً نقترح صيغة جديدة للتطبيق اللاتمددي المعمم على نحو تكون فيه هذه المتتاليات متكافئة أيضاً . In this paper, we prove that the sequences (Mann, Ishikawa , Noor) are equivalent for the class of weak contractive mappings defined on closed, convex subsets of arbitrar Banach spaces ,and we prove that the equivalence extends to the generalized non expansive mappings with the conditions : Finally, we define new formula for generalized non expansive mappings such as that these sequences are equivalent.